SISTEM INFORMASI PENGADAAN BAHAN PRODUKSI BETON SIAP PAKAI (READYMIX) PADA PT. SCG READYMIX INDONESIA PLANT CILEGON - Waliadi Gunawan; Yuli Setyaningsih (Program Studi Sistem Informasi, Universitas Banten Jaya, 2019)
In the system of readymix concrete production material procurement at PT. SCG Indonesia Readymix Plant Cilegon, the company was still conduced by manual system. It used filing system that stored in the production division. The entry system used the form that submitted directly, therefore in making report, it needed inefficient time and created difficulties for the clerk to input the data manually in receiving production material. If the company required the data about material production, they must seek the data from the stack of existing archive. Besides that, the report generated less efficient because in the recording the data was conducted by employee that still used system manually. Therefore, sometime the result of report contained some errors. To overcome the existing problems, it is necessary to use the computer based of production materials procurement information system. The aims were 1) to facilitate the procurement of material for the production process, 2) to make easier for the employees to find out and to enter the necessary data of production materials procurement, 3) to create the effective and efficient work, and 4) to use in making report of production material procurement quickly and easily.